Preliminary Study and Characterization of Pozzolanic Reaction-based Low-Energy Cement using 41 wt% Ca(OH)2 ÃâÃâ 41 wt% Metakaolin ÃâÃâ 18 wt% Gypsum - Setyo Nugroho (NIM : 13713025), Adhi
Indonesia is doing infrastructure building program especially ready-to-live houses. One of the important construction materials is cement. Conventional cement production through pyroprocessing using temperature of 1500oC causes environmental pollution by exhaust gas and very finely silica powder, and also consumes high energy. Reseachers is studying how to lowering the energy consumption for production processes. One of the alternative wayout is pozzolanic reaction-based low-energy cement using Ca(OH)2-metakaolin-gypsum mixtures. When cement is mixed with water, hydration process occurs resulting calcium silicate hydrate product, which contributes to the strength of a structure. This research started by casting Ca(OH)2/SiO2 mixtures with 0.2, 0.4, 0.6, and 1 ratios as a pre-trial. The compressive strength of the hydrated products in age 14 is about 1 MPa, too low strength. The identified phases are calcite, quartz, and portlandite. Then, it continued by using 41 wt% Ca(OH)2 – 41 wt% metakaolin – 18 wt% gypsum mixtures, under ponding curing method with 50oC and 20oC curing temperatures. The highest compressive strength of hydrated product is 23.44 MPa, with identified phases are ettringite, calcite, and quartz. Further analysis showed that ettringite contributes to the strength. It can be concluded that pozzolanic reaction occurs in 41 wt% Ca(OH)2 – 41 wt% metakaolin – 18 wt% gypsum mixtures. Thus, it can be used as substitute for conventional cement. v